Nitrogen mitigation scenarios to reduce coastal eutrophication. Issue 4 (17th November 2022) - Malik, Wafa; Oehler, François; Sgro, Lea; Durand, Patrick
Abstract: Macroalgal blooms in coastal areas, which pose unique risks to the environment, citizens, stakeholders, and the economy, mainly are due to nitrate pollution in rivers. The Saint‐Brieuc Bay has some of the largest algal blooms in Brittany (western France). It is fed by three catchments—Gouessant (420 km 2 ), Gouet (256 km 2 ), and Anse d'Yffiniac (130 km 2 )—characterized by an oceanic climate and mixed‐farming systems with high livestock density. The main objective of this study was to assess the ability of nitrogen (N) mitigation scenarios to reduce N emissions to coastal water using the spatially distributed agrohydrological model TNT2. Once TNT2 was calibrated and validated for the catchments, scenarios were simulated for them from 2008 through 2035: (a) reference (REF) scenario, (b) agricultural management practices (AMP) scenario (i.e., changes to mineral and organic N fertilization, catch crops, and crop rotations), (c) increasing percentages of agricultural land conversion (ALC) into unmanaged grassland from downhill to uphill, and (d) scenarios that combined AMP and ALC. Results showed that the AMP scenario could reduce N load in the bay by 31% vs. the REF scenario. The ALC scenario was much more effective when located downhill, with >50% of maximum effectiveness achieved with 10% of agricultural land converted. These results varied strongly among catchments. Because reducing coastal eutrophication requires a drastic decrease in N loads, we recommend combining AMP and ALC scenarios to achieve good environmental status. The study illustrates the TNT2 model's ability to simulate complex scenarios and guide mitigation policy. Core Ideas: Agricultural N mitigation is challenging for reducing coastal eutrophication. Spatial targeting in catchments decreased nitrate load greatly. Drastic changes to management practices would reduce nitrate load by 31%. The TNT2 model is useful for assessing complex N‐mitigation scenarios and their response time.